Numerical Analysis of the Behavior of Compacted and Natural Unsaturated Tropical Soils - Silveira, Isabela Augusto [UNESP] (2019)
Several regions of countries with tropical climate exhibit alternation between dry and rainy seasons and, these countries also exhibit geological processes that create ideal conditions for the formation of thick layers of unsaturated porous soils. These soils may present collapsible behavior, that is, volumetric deformations due to the wetting of the soil without any variation of applied load. In this research, results of oedometer tests with suction control using the axis translation technique in both natural and compacted soil are presented and simulated numerically. The CODE_BRIGHT program was used for this purpose in coupled hydro-mechanical analysis, and the Barcelona Basic Model was used as a mechanical constitutive model. In the numerical simulations carried out for the natural and compacted soil, the experimental results were suitable to the numerical results for the oedometer tests with constant suction throughout the entire test. The numerical simulations carried out for the tests with collapse in natural soil, that is, with gradual reduction of suction in a certain tension, presented considerable dispersion. The paper also presents important considerations about the effect of compaction as an improvement of the collapsible soil in relation to the volume variation and the effect of suction on the behavior of the soil.